Pengembangan Media Pembelajaran Pop-Up Book Pada Pembelajaran IPA Kelas V SD Negeri 46 Lubuklinggau - Rahmadhani, Rezky Putri; Lokaria, Eka; Krisnawati, Yuni (LP4MK STKIP PGRI Lubuklinggau, 2024)
This research aims to determine the validity, practicality and effectiveness of Learning Media Pop-Up Book Class V Science at SD Negeri 46 Lubuk Linggau which was developed. This type of research is Research and Development with a development model ADDIE. The research subjects consisted of experts, teachers and class V students at SDN 46 Lubuklinggau. Data was collected through observation, interviews, questionnaires and tests. Based on the results of validation carried out by linguists, material experts and media experts, the Pop-Up Book in class V science learning was declared to meet valid criteria with an average score of 0.91. Analysis of the practicality sheet assessment for educators and students meets the practical criteria with a score of 86.81%. Then the analysis of the effectiveness assessment is obtained by a score N-Gain an average of 0.74 in the high category. Based on the research results, it can be concluded that Learning Media Pop-Up Book In Class V science learning, it was proven to be valid, practical and effective so it is suitable for use in science learning, material on changes in the shape of objects for class V SDN 46 Lubuklinggau